The Untapped Potential of Ethno-Tourism in Ulytau Region - MUKATOVA, Rabiga; MUSSINA, Kamshat; RODRÍGUEZ, Maribel (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022DO - 10.14505/jemt.v13.6(62).02, 2022)
Kazakhstan is a unique country, with beautiful nature, original culture, and traditions. Ulytau region is the historical and geographical center of the Republic of Kazakhstan, the cradle of the Kazakh people. It is one of the epicenters of steppe civilization and nomadic culture. Ulytau is a unique region with over 700 registered monuments of history and culture and has a great potential to develop ethno-tourism. According to conducted survey over a 10-month period from January to October 2021, it was revealed that a huge part of tourists doesn’t know about this destination and features of this region and would like to visit this region with ethno-cultural purposes. This article shows the results of the study, the main constraining factors, and mechanisms for the implementation of ethno-tourism. These findings contribute to a better understanding of the involvement of tourists in visiting a tourist destination for the purpose of ethno-tourism, and a number of recommendations are proposed for key stakeholders.